546 COMMUNITY HEALTH INITIATIVE BY UNIVERSITY STUDENTS: SYSTEMIC CHART REVIEW 2006. (1st January 2006) - Kryskow, P.; Argent, C.; Tan, C.; Morgan, A.; Hardial, J.; Granger, P.
Abstract : CHIUS (Community Health Initiative by University Students) is an interdisciplinary, student-run program at the downtown community health clinic (DCHC) in the downtown east side (DTES) area of Vancouver. Students from different health care disciplines work together to provide patient care under the supervision of their respective health care professions. The student clinic runs every weekend and generally involves an abundance of clinical and social encounters. After treating patients, medical students complete patient charts in the SOAP format, and all team members complete a patient encounter log. Due to growth of the team, a new clinic site, and changes to the structure of CHIUS in the last 4 years, as part of our continuing responsibility to ensure the delivery of quality patient care, student education, and public safety, we are doing a systemic review of the patient charts and encounter logs of the last 4 years. With this, we hope to confirm or further describe the demographics and needs of our patients. We hope that the outcomes of our continuing efforts will allow us to make recommendations to CHIUS that result in further tailoring of programs to meet patient needs and optimize student learning. These results are also important to ensure that the patient's encounter with the clinic results in the most appropriate care and that we are meeting the patient's concerns.